DISTORTED PERCEPTION - INSIGHTS INTO ALICE IN WONDERLAND SYNDROME - Karolina Drygała,; Gabriela Barszcz,; Natalia Bębenek,; Monika Błądek,; Sylwia Wit,; Paulina Frączkiewicz,; Izabela Harpula,; Radosław Ramotowski,; Justyna Bogdan,; Benedykt Baljon,; Patryk Brzezicki, (International Journal of Innovative Technologies in Social Science, 2025)
Research objectives: Alice in Wonderland syndrome (AIWS) is a perceptual disorder characterized by distortions of visual perception (metamorphopsias), the body schema and the experience of time. The aim of this study is to summarise the current state of knowledge about this disease.Methods: The PubMed database was searched using the term: ”Alice in Wonderland Syndrome”. After analysis, 34 papers were included in the review.Key findings: Affected individuals can experience visual illusions, including dysmetropsia, namely  micropsia (objects appear small), macropsia (objects appear large), teleopsia (objects appear further away than they are). In addition to these alterations in perception, patients might have distorted experience of time, disorders of consciousness such as feelings of derealization, depersonalization. There are numerous disorders, intoxications and other conditions that have been described in the context of AIWS. In childhood, AIWS is most commonly linked with migraine and encephalitis caused by Epstein–Barr virus. Migraines are frequently thought to be the main cause in adults. Other possible underlying conditions of the AIWS include infections, epilepsy and intoxications.Treatment must be directed toward the presumed underlying disease whenever it is deemed necessary and beneficial.Conclusions: Alice in Wonderland syndrome is still poorly known condition and probably misdiagnosed for the lack of clear and universally accepted diagnostic criteria. It can occur at any age, but appears to be more common during childhood and adolescence. The most common symptoms include: distortions of the size, mass or shape of the patient’s own body.